IMPLEMENTASI SISTEM PENGENDALI WASTAFEL CUCI TANGAN BERBASIS IoT MENGGUNAKAN PLATFORM BLNYK - Udoyono, Kodar; Rizky, Muhammad Alif (STMIK Subang, 2023)
The enhancement of cleanliness and sanitation has become a paramount concern in modern society, particularly in the face of a global pandemic. In this context, this research proposes and implements an Internet of Things (IoT)-based handwashing sink control system using the BLNYK platform, ESP8266 module, infrared proximity sensor E-18-DNK, solenoid valve DC 12V, and LM259 stepdown. The system is designed to provide an efficient and hygienic handwashing experience. The ESP8266 module serves as the central brain connected to the BLNYK platform, enabling users to remotely access and control the sink via mobile devices or computers. The infrared proximity sensor E-18-DNK detects the presence of user hands, triggering the solenoid valve DC 12V to automatically dispense water. Additionally, the LM259 stepdown is utilized to regulate voltage and optimize power consumption, making the system energy-efficient. Sink usage data and usage statistics can be accessed through the BLNYK platform, facilitating efficient monitoring and analysis. Test results demonstrate the system's reliability in accurately detecting hands and providing a swift response in opening the solenoid valve. Furthermore, the implementation of the LM259 stepdown successfully optimizes the power consumption of the system, making it an energy-efficient solution. Thus, this system can serve as a model for further development in creating IoT-based intelligent solutions to enhance cleanliness and sanitation in various environments, including households, public spaces, and healthcare facilities.